Optimized Nail for Penetration Test on Lithium-Ion Cells and Its Utilization for the Validation of a Multilayer Electro-Thermal Model - Luigi Aiello; Gregor Gstrein; Simon Erker; Bernhard Kaltenegger; Christian Ellersdorfer; Wolfgang Sinz (Batteries, 2022)
Nail penetration is one of the most critical scenarios for a lithium-ion cell: it involves the superposition of electrical, thermal and mechanical abusive loads. When an electrically conductive nail is introduced into the active layers of a lithium-ion cell, an electric short circuit takes place between the conductive components (electrodes and current collectors). Hence, for this load case, electro-thermal modeling must be performed considering each and every layer of the cell in order to predict the electric quantities and the cell temperature (with numerical models). When standard conic nails are used, as is typical for this class of tests, the electrical contact between conductive components and the nail itself suffers of poor reproducibility mainly due to the separator that interposes between the electrically conductive components. This phenomenon makes it difficult to validate electro-thermal models, since the electrical contact between nail and lithium-ion cell parts cannot be safely determined. In this work, an alternative nail with an optimized ratio between the external surface and volume is presented to overcome this issue. To demonstrate the effectiveness of the designed nail, five tests (with the same conditions) were conducted on five commercial lithium-ion pouch cells, monitoring the tabs voltage and surface temperature. In all tests, thermal runaway was reached within 30 s and the tabs voltage showed comparable behavior, indicating that the short circuit values for all five repetitions were similar. The investigation included the implementation of a detailed layers model to demonstrate how the validation of such model would be possible with the novel data.